Is no evidence of disease activity an achievable goal in MS patients on intramuscular interferon beta-1a treatment over long-term follow-up? - Uher, Tomas; Havrdova, Eva; Sobisek, Lukas; Krasensky, Jan; Vaneckova, Manuela; Seidl, Zdenek; Tyblova, Michaela; Ramasamy, Deepa; Zivadinov, Robert; Horakova, Dana (Multiple sclerosis (Houndmills, Basingstoke, England), 2017)
BACKGROUND: No evidence of disease activity (NEDA) has been proposed as a new treatment goal in multiple sclerosis (MS). NEDA-3 status is defined as the absence of magnetic resonance imaging (MRI; new/enlarging/enhancing lesions and increased whole brain volume loss in NEDA-4) and clinical disease activity. OBJECTIVES: To investigate the persistence of NEDA status over long-term follow-up in MS patients treated with weekly intramuscular interferon beta-1a. METHODS: We included 192 patients after the first demyelinating event suggestive of MS, that is, clinically isolated syndrome (CIS) and 162 relapsing-remitting MS (RRMS) patients. RESULTS: NEDA-3 status was observed in 40.1% of CIS and 20.4% of RRMS patients after 1 year. After 4 years, 10.1% of CIS patients had NEDA-3 status. After 10 years, none of the RRMS patients had NEDA-3 status. Only 4.6% of CIS and 1.0% of RRMS patients maintained NEDA-4 status after 4 years. Loss of NEDA-3 status after the first year was associated with a higher risk of disability progression (hazard ratio (HR) = 2.3-4.0; p = 0.005-0.03) over 6 years. CONCLUSIONS: Despite intramuscular interferon beta-1a treatment, loss of NEDA status occurred in the vast majority of individuals. Loss of NEDA status during the first year was associated with disability progression over long-term follow-up; however, specificity for individual patient was low.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; lidé středního věku; interferon beta; Multiple Sclerosis; Disease Progression; no evidence of disease activity; Interferon-beta; Female; mladý dospělý; dospělí; Goals; lidé; magnetic resonance imaging; disability; mladiství; časové faktory; Adult; Multiple sclerosis; Follow-Up Studies; ženské pohlaví; roztroušená skleróza; Male; Middle Aged; Adolescent; interferons; Young Adult; progrese nemoci; cíle; mužské pohlaví; brain atrophy; Time Factors; následné studie; Interferon beta-1a; interferon beta 1a